Exploring Organizational Identity and Interpersonal Conflict in Sport Organizations - Shannon Kerwin (Journal of Applied Sports Management, 2013)
Interpersonal conflict is a dysfunctional group process that requires scholarly attention. Despite support for this claim, there is a gap in theoretical knowledge regarding the antecedent conditions to interpersonal disagreement in sport organizations. As such, the tenets of social identity theory were used to explore if and how organizational identity influences the perception of conflict in the regional sport commission context. A multi-method qualitative approach was adopted to serve the purpose of this study. The findings indicate that organizational identity is present, in-group/out-group identity formation contributes to status conflict, and that both formal and informal leadership play a role in the development of organizational identity and the management of in-group/out-group formation within this context. These findings have implications for how identity is conceptualized and measured in the sport management context and support the continued examination of the role of social identity as an antecedent condition for interpersonal conflict.
Keywords: Conflict; identity; voluntary-based sport organizations